Magnetni gradiometer z ultrahladnimi atomi cezija na osnovi ene same Stern-Gerlachove slike - Gosar, Katja (Matrika, 2020)
The magnetic field can be measured through Larmor precession of the atomic magnetization. In this article the dynamics of magnetization in magnetic fields is explained, including Larmor precession and Rabi oscillations, and the use of the Stern-Gerlach method to probe the magnetization projection of cold cesium atoms. Experimental observations of these phenomena are presented, including a demonstration of a magnetic gradiometer capable of measuring one component of the magnetic field gradient tensor in a single shot.
Keywords: Larmor precession; Larmorjeva precesija; magnetic field; magnetic field gradient tensor; magnetic gradiometer; magnetizacije; magnetization; magnetni gradiometer; magnetno polje; Rabi oscillation; Rabijeva oscilacija; tenzor magnetnega gradienta